INDÚSTRIA DA CONSTRUÇÃO SUSTENTÁVEL: UMA ANÁLISE DA CERTIFICAÇÃO LEED NO MERCADO BRASILEIRO - Oliveira, Marcos Lucas de; Ruppenthal, Janis Elisa; Vergara, Lizandra Garcia Lupi (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Sustainable buildings feature a technology migration that aims to reduce the impact of buildings on the built environment, future generations and their environment. In this sense, environmental certifications can be used as political or marketing instruments in social, economic and environmental development. Therefore, the present study describes the relationship of the LEED certification system, focusing on the Brazilian market. The methodology used is a descriptive research. As a result, the study shows that the Brazil's expressive results put it in fourth place in the worldwide list of LEED sustainable certifications. It was concluded that the corporate strategies for sustainable construction in Brazil are concentrated to highstandard projects, since the country has not yet understood the real value of sustainability, which is not only environmental, it has to be technical and economic.